Peran Guru Sebagai Administrator di Sekolah - Dian Suci Oktafiami; Miftahir Rizqa (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Teachers have an important role in education, not only as teachers, but also as administrators in schools. This dual role requires teachers to have various competencies, both in pedagogy and management. As administrators, teachers have the responsibility to manage various important aspects of the school, such as: Developing lesson plans, assessing student learning progress, and making learning outcome reports. Managing classroom budgets, creating financial reports and applying for funds. Managing teacher and staff data, assisting with the recruitment process and resolving staffing issues. Maintain and care for school facilities and infrastructure, make damage reports, and apply for procurement of goods. Establish communication with parents, school committees and the surrounding community. In the context of education, the role of teachers as administrators in schools plays a very important role in managing various aspects of school activities. Teachers are not only tasked with teaching, but also as leaders in organizing school administration, including curriculum planning, supervising student activities and managing resources. With good administrative skills, teachers can create an effective and efficient learning environment, ensure all processes run smoothly, and make a positive contribution to the school's progress and overall student achievement.